PENGERTIAN, TUJUAN, METODE DAN RUANG LINGKUP PERBANDINGAN PENDIDIKAN - Abdul Wahab Syakhrani; Maulana Maulana; Ilhamnor Ilhamnor; M. Nur Fazri; Muhammad Azkia (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
The purpose of comparative education is to find out what power differences have given rise to the different forms of education systems in the world. In other words, in one country, for example, religious power is the main driving factor and the basis for the formation of the education system, while in another country social factors are the foundation of an education system. And it has also been explained that there are 6 methods used in comparative education, namely: Historical, Descriptive, Statistical, Philosophical, Comparative, and the last one is Quasi-experimental. For the last one, which is discussing the scope of comparative education where we have explained there are explanations according to 3 experts, namely the first according to William W. Brickman then according to Nicholas Hans and the last according to I.L. Kanderl.